Efektywny nadzór korporacyjny - potrzeba czy mit? - Dziworska, Krystyna; Górczyńska, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the environment of globalization and rising enterprise competitiveness in Europe and worldwide,corporate governance has became an important factor indicating country position on internationalmarket. We are at the beginning of the process of developing and implementing standards ofcorporate governance in Poland. There is a discussion over the corporate governance in many differentsocieties. The article is an element of this discussion. The authors focuses on the model of corporategovernance in Poland and the conditions of its effectiveness and efficiency.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 154-164